The Relationship Between Social Status and Stunting Incidence at the Biru Community Health Center in Bone Regency in 2025 - Febrianti; Yusriani; Sumiaty; Andi Asrina; Fairus Prihatin Idris; Muh. Khidri Alwi (Poltanesa, 2025)
Stunting remains a major public health challenge in Indonesia, particularly in rural areas such as Bone Regency. It reflects chronic malnutrition that affects physical growth, cognitive development, and long-term productivity. This study aimed to analyze the relationship between social status and stunting incidence in the working area of the Biru Community Health Center, Bone Regency, in 2025. The research was conducted using an analytical observational design with a cross-sectional approach. The study population consisted of 1,588 toddlers aged 24–59 months, with a sample of 107 respondents selected using the Lemeshow formula. Data were collected through structured interviews using validated questionnaires and secondary data from the health center and the district health office. Data analysis employed the Chi-square test and logistic regression to determine significant associations and dominant influencing factors. The results revealed a significant relationship between social status and stunting incidence (p = 0.030). Children from families with low social status had a higher risk of stunting (60.9%) compared to those from families with higher social status (35.7%). These findings indicate that educational level, parental occupation, and social participation are key social determinants influencing child nutritional status. The study emphasizes the need to strengthen community-based health interventions, including nutrition education, maternal empowerment, and active participation in posyandu activities, to reduce stunting prevalence. Strengthening collaboration among health workers, local government, and community leaders is essential to improve family health literacy and ensure sustainable stunting prevention in the Bone Regency area.